2022
DOI: 10.1177/15356841221129791
|View full text |Cite
|
Sign up to set email alerts
|

“You Have to Prove that You’re Homeless”: Vulnerability and Gatekeeping in Public Housing Prioritization Policies

Abstract: Building on theories of symbolic boundaries, this article explores the role of the state as gatekeeper to social programs, such as public housing. Using interviews with 75 randomly sampled households living in public housing in Honolulu County, we link contemporary research on gatekeeping with decades of work on how housing policy drives residential outcomes for marginalized groups. In particular, we consider the largely unexamined case of “local preferences,” which fast-track certain individuals into social p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
(96 reference statements)
2
5
0
Order By: Relevance
“…Many respondents were also conscious of the costs of category-based prioritization on applicants, which they often gleaned when talking to applicants seeking updates on their waitlist position. Consistent with research on applicant perspectives (Keene et al 2021;Rita et al 2022), officials observed that deviating from a first-come first-served approach generated distrust and confusion. As an official in a major U.S. city pointed out, "People really know when they went on that list, and our applicants tend to know each other, so you get a lot of, 'Well, my friend applied when I did, how come this?"'…”
Section: Part Iii: Interviews With Housing Authority Officials and Co...supporting
confidence: 52%
See 4 more Smart Citations
“…Many respondents were also conscious of the costs of category-based prioritization on applicants, which they often gleaned when talking to applicants seeking updates on their waitlist position. Consistent with research on applicant perspectives (Keene et al 2021;Rita et al 2022), officials observed that deviating from a first-come first-served approach generated distrust and confusion. As an official in a major U.S. city pointed out, "People really know when they went on that list, and our applicants tend to know each other, so you get a lot of, 'Well, my friend applied when I did, how come this?"'…”
Section: Part Iii: Interviews With Housing Authority Officials and Co...supporting
confidence: 52%
“…Many respondents were also conscious of the costs of category-based prioritization on applicants, which they often gleaned when talking to applicants seeking updates on their waitlist position. Consistent with research on applicant perspectives (Keene et al 2021; Rita et al 2022), officials observed that deviating from a first-come first-served approach generated distrust and confusion. As an official in a major U.S. city pointed out, “People really know when they went on that list, and our applicants tend to know each other, so you get a lot of, ‘Well, my friend applied when I did, how come this?”’ Another respondent, who directed several small housing authorities in highly conservative areas, explained how preferences lead to difficult conversations:It’s an awkward thing to have to administer the program and have to explain to people why they were 90 in the waiting list last month, and now they’re 120. .…”
Section: Part Iii: Interviews With Housing Authority Officials and Co...supporting
confidence: 52%
See 3 more Smart Citations